Ceste figure contient tout le royaulme de France. Cartography and national identity in France at the end of the Hundred Years War - Serchuk, Camille (Journal of Medieval History, 2007)
This paper examines a little known map of France made around the middle of the fifteenth century, for a genealogical manuscript of the text known as A tous nobles, conserved today as Bibliothèque nationale de France [BnF] MS fr. 4991. It argues that the map's prominence in the manuscript articulates a notion of French identity based on a bond to the territory of France rather than on fealty to its king. Using other images from the manuscript, it considers the importance of geography to the emergence of French national sentiment at the time of the Hundred Years War. © 2007 Elsevier Ltd. All rights reserved.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/009-140-123-972-806 tex.type: [object Object]
Keywords: A tous nobles; Bibliotheque nationale de France MS fr. 4991; Débat des hérauts d'armes de France et d'Angleterre; Evesham Map; Geography; Grandes Chroniques de France; Marcomir; Medieval cartography; National identity; Norman Conquest; Polemical literature; Remanieurs; dept.art